City As Landscape : A Post Post-Modern View of Design and Planning. - Turner, Tom. (Oxford : CRC Press LLC, 1995)
In twenty essays, this book covers aspects of planning, architecture, urban design, landscape architecture, park and garden design. Their approach, described as post-postmodern, is a challenge to the 'anything goes' eclecticism of the merely postmodern.
Cover -- Title Page -- Copyright Page -- Table of Contents -- PREFACE -- ACKNOWLEDGEMENTS -- THEORIES -- 1 Post-postmodernism -- 2 Design and planning methods -- 3 'A city is not a tree': it is a landscape -- 4 Patterns in use -- footprints in the sand -- PLANNING -- 5 GIS, structuralism, the birth, the death and the life of planning -- 6 CD-plans -- 7 Metaphorical plans -- 8 Eco-city plans -- URBANISM -- 9 Architecture, language and the environment -- 10 Context and design -- 11 Deconstructing the constructive professions -- 12 The tragedy of feminine planning and design -- LANDSCAPE DESIGN -- 13 The blood of philosopher-kings -- 14 Studio craft -- OPEN SPACE PLANNING -- 15 Parks and boundless space -- 16 Harlequin space -- 17 Greenways and otherways -- 18 Reading Parc de la Villette -- GARDENS -- 19 Revolutions in the garden -- 20 Gardening with ideas -- REFERENCES -- INDEX.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Philosophy; Electronic books